Urban ethnobotany and phytochemical profiles of plants cultivated by Chinese migrants in Buenos Aires, Argentina - Puentes, Jeremias; Azañedo-Atoche, Yender Krosvy; Duarte Galhardo de Albuquerque, Ricardo Diego; Ganoza-Yupanqui, Mayar Luis (Ethnobotany Research and Applications, 2026)
Background: In the Area Metropolitana de Buenos Aires, Chinese farmers grow fresh plants that supply Buenos Aires’ Chinatown. These crops can be considered Neglected and Underutilized Species since they are little known to the majority of the urban population, who are unaware of their uses and nutritional value. The main objective of this work is to update the ethnobotanical data on plants grown organically and conventionally by Chinese farmers and to determine their phytochemical profile. Methods: Fieldwork was conducted at two sites in Buenos Aires where two Chinese producers grow plants linked to the traditions of their country. The methodology used consisted of ethnobotanical walks, free listings, and open and semi-structured interviews with farmers and community members. The phytochemical profiles were analyzed using UHPLC-MS/MS, and the data were processed using multivariate analysis to evaluate the differences between the cultivation systems. Results: Brassica juncea and B. rapa var. chinensis are the most common species in Chinatown and are sold year-round. They are grown conventionally and organically, are linked to Asian culinary traditions, and are produced from imported seeds. Organic crops showed higher concentrations of kaempferol and isorhamnetin derivatives (compounds associated with antioxidant and hepatoprotective properties), which differentiates them from conventional samples. Conclusions: Urban ethnobotany highlights the role of migrant communities in increasing local agrobiodiversity. Organic farming not only promotes sustainable agriculture, but also improves the biochemical quality of crops. Keywords: Biocultural diversity, Botanical Knowledge, Organic agriculture, Pearson correlation, PCA, PLS-DA, UHPLC-PDA.